2008
DOI: 10.1007/s11200-008-0038-7
|View full text |Cite
|
Sign up to set email alerts
|

Derived gravity field of the seismogenic upper crust of SE Germany and West Bohemia and its comparison with seismicity

Abstract: The gravity field of the seismogenic upper crust was derived from the Bouguer gravity map by applying the Butterworth high-pass filter in the wave-number domain. The cutoff wavelength of the filter was 110 km, to pass the gravity signals of structures within the 18 km thick seismogenic layer. The derived residual gravity map reveals potential stress concentrating structures, which may cause seismicity provided they lie within the existing zones of weakness. Furthermore we derived a shaded relief map of the hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…At the same time, geophysical and geological observations in the Eger Graben area led to a formal definition of the surface demonstration of the Saxothuringian/Teplá-Barrandian boundary, which was then designated as the "Litoměřice deep fault" (Šťovíčková 1973). Gravimetric survey along this fault zone has revealed a chain of positive gravity anomalies and a steep gravity gradient towards the northwest indicating the boundary between low-density rocks of the Saxothuringian Zone and high-density rocks of the Teplá-Barrandian Zone (Šťovíčková 1973;Blížkovský et al 1994;Švancara et al 2008;Sedlák et al 2009). Seismic survey in the area of the Saxothuringian/Teplá-Barrandian boundary by Plomerová et al (2007) and has shown differences in orientation of the mantle fabric in these large-scale zones and led to delimitation of their contact in the mantle lithosphere.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, geophysical and geological observations in the Eger Graben area led to a formal definition of the surface demonstration of the Saxothuringian/Teplá-Barrandian boundary, which was then designated as the "Litoměřice deep fault" (Šťovíčková 1973). Gravimetric survey along this fault zone has revealed a chain of positive gravity anomalies and a steep gravity gradient towards the northwest indicating the boundary between low-density rocks of the Saxothuringian Zone and high-density rocks of the Teplá-Barrandian Zone (Šťovíčková 1973;Blížkovský et al 1994;Švancara et al 2008;Sedlák et al 2009). Seismic survey in the area of the Saxothuringian/Teplá-Barrandian boundary by Plomerová et al (2007) and has shown differences in orientation of the mantle fabric in these large-scale zones and led to delimitation of their contact in the mantle lithosphere.…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that segments a, b, c, f, g and i were the more active ones in recent history (Pleistocene -Holocene?). Unfortunately, only segments a and b have been previously studied by palaeoseismology or detailed geophysics so far (Procházková et al, 1998;Švancara et al, 2008;Fischer et al, 2012;Halpaap et al, 2017;Blecha et al, 2018;Štěpančíková et al, 2019). These studies agree on that the youngest tectonic activity occurred in this NW part of the MLF.…”
Section: Segmentation Of the Mlf And Evaluation Of The Methods Usedmentioning
confidence: 77%
“…However, the character of the fault escarpment varies in different parts of the MLF, it is possible to observe different grades of tectonic facets evolution, water stream erosion etc. This can indicate a complicated tectonic history and possibly the difference in age and rate of the tectonic movements in the particular segments of the MLF (Badura et al, 2007;Švancara et al, 2008). The MLF separates two distinct types of relief (Fischer et al, 2012): higher terrain on the eastern side and lower on the western.…”
Section: Geomorphological Settingmentioning
confidence: 99%
See 1 more Smart Citation